Capturing the dynamics of amazonian wetlands using synthetic aperture radar lessons learned and future directions - Silva, Thiago Sanna Freire [UNESP]; Melack, John; Streher, Annia Susin; Ferreira-Ferreira, Jefferson; de Almeida Furtado, Luiz Felipe (Taylor & Francis, 2015)
The Amazon basin comprises the largest continuous expanse of tropical forests in the world, covering about 78% of the basin’s 7 million km2 (Goulding et al. 2003). Despite the predominance of upland (“terra firme”) forests, the Amazon is recognized by its large network of large rivers, fueled by precipitation that can average up to 3500 mm/year, with annual extremes of 4500 mm or more (Fisch et al. 1998; Satyamurty et al. 2009). Open water surfaces can reach up to 3% of the entire area for the central Amazon main stem (Arraut et al. 2013), and the entire basin has an average discharge of 209,000 m3/s from its more than 6 million km2 of drained area (Latrubesse et al. 2005).